Bladder neck leiomyoma presenting with acute retention of urine in an elderly female - Santosh Kumar Agrawal; Pallavi Agrawal; Shweta Paliwal; Chandrajeet Yadav (Wolters Kluwer Medknow Publications, 2014)
Acute painful retention of urine in a female is uncommon presentations. Bladder neck tumor presenting as acute painful retentions is rare clinical scenario. We present a case of the urinary bladder neck leiomyoma in a 45-year-old peri-menopausal female who presented with acute painful retention of urine without prior history of lower urinary tract symptoms. Patient was managed with cystoscopy and transurethral endoscopic resection of the tumor.